Cyber security laws and safety in e-commerce in India - A. K. Kashyap; M. Chaudhary (Law and Safety, 2023)
In today’s information technology age, the issue of cyber Security is a complicated and fascinating area of law. The phenomenal growth and development of e-commerce in India is astounding. However, with the rising dependence on internet commerce, the dangers of fraud and security and trust problems have become severe impediments. Creating robust legal and regulatory frameworks that meet the growing concerns about online fraud, data security, and intellectual property protection in both local and international business contexts is critical. The e-commerce sector, like any expanding business, confronts various obstacles, primarily due to an inadequate and inefficient legal and regulatory framework that fails to guarantee the rights and duties of all players engaged sufficiently. To protect user data, tackle cyber threats, and maintain customer trust, e-commerce enterprises must comply with legal regulations. In India, cybersecurity governance falls under the Information Technology Act of 2000, regulating e-commerce, electronic contracts, data protection, and cybercrimes. The imminent passage of the Personal Data Protection Bill, 2019, is expected after ongoing review. The Indian Penal Code addresses unauthorized access, hacking, identity theft, phishing, and computer virus dissemination. The Reserve Bank of India oversees online payment and financial security, mandating two-factor authentication, encryption, and secure payment channels. CERT-In coordinates national cybersecurity incidents, while electronic signatures and digital certificates hold legal recognition. Intellectual Property Laws regulate online violations of patents, copyrights, and trademarks. The Indian government also enforces cybersecurity standards for enterprises and organizations, covering IT infrastructure and incident response. Nonetheless, further steps must be taken to improve the efficiency of India’s cyber security regulations. This research study uses a doctrinal and analytical approach to examine India’s present Cyber Security Laws and Guidelines. It assesses their effectiveness in addressing legal concerns with Security, privacy, and data protection inside the country. It also evaluates the legal structure that governs the link between e-commerce and Cyber Laws in India. This research will provide a thorough overview of the present condition of cyber security regulations in India, setting the way for prospective reforms and progress in this critical area.